Booming Startup: A Revolutionary Strategy of Curriculum Management for Founders of Vocational School Graduates - Subkhi, Imam; Azkia’, Ahmad Azkal (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to interpret the revolutionary strategy of curriculum management in producing founder graduates of vocational schools.   The research design used is qualitative research with a case study method. The sources of informants in this study consisted of principals, teachers, and curriculum managers. Data collection in this study was conducted through three primary methods: in-depth interviews, participatory observation, and document analysis. The results of this study indicate that the revolutionary strategy of curriculum management at SMKN Darul Ulum Muncar has succeeded in producing founder graduates through Successful Entrepreneur Collaboration in Curriculum Preparation, Golden Opportunities for Vocational Graduates at Job Fair events, and Curriculum Innovation Based on Fisheries Agribusiness. The novelty in this research is the revolutionary strategy of curriculum management that contributes to producing vocational graduates. The contribution of this research shows that the application of revolutionary curriculum management strategies can produce successful graduates for SMKN Darul Ulum Muncar.